2012
DOI: 10.1164/rccm.201201-0003oc
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome-regulated Cytokines Are Critical Mediators of Acute Lung Injury

Abstract: Rationale: Despite advances in clinical management, there are currently no reliable diagnostic and therapeutic targets for acute respiratory distress syndrome (ARDS). The inflammasome/caspase-1 pathway regulates the maturation and secretion of proinflammatory cytokines (e.g., IL-18). IL-18 is associated with injury in animal models of systemic inflammation. Objectives: We sought to determine the contribution of the inflammasome pathway in experimental acute lung injury and human ARDS. Methods: We performed com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
441
3
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(470 citation statements)
references
References 50 publications
(54 reference statements)
19
441
3
7
Order By: Relevance
“…However, IL-18 demonstrated a clear trend to increased levels after trauma, indicating at findings from others that have represented the importance of IL-18 as a promising biomarkers for predicting morbidity and mortality of ARDS [52]. Similar findings were reported by Dolinay et al (2012), showing that patients with trauma-or sepsis-induced ARDS had increased IL-18 levels, which correlated with increased in-hospital mortality [54]. Additional studies to validate these findings are needed.…”
Section: Discussionsupporting
confidence: 64%
“…However, IL-18 demonstrated a clear trend to increased levels after trauma, indicating at findings from others that have represented the importance of IL-18 as a promising biomarkers for predicting morbidity and mortality of ARDS [52]. Similar findings were reported by Dolinay et al (2012), showing that patients with trauma-or sepsis-induced ARDS had increased IL-18 levels, which correlated with increased in-hospital mortality [54]. Additional studies to validate these findings are needed.…”
Section: Discussionsupporting
confidence: 64%
“…Recent studies suggest that inflammasome-related cytokines, including IL-18, play important roles in acute lung injury. 4 Arndt et al reported that IL-18 may play a role in modulating the development of acute lung injury during endotoxemia. 5 As we reported that IL-18 delayed human neutrophil apoptosis in vitro, 6 the effect of IL-18 on neutrophil apoptosis may be a key factor in acute lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β was generated presumably by activation of the inflammasome, 19 which has been linked to the pathogenesis of ARDS. 20 This inhibition of proinflammatory cytokines has also been …”
Section: Discussionmentioning
confidence: 91%